1993
DOI: 10.1055/s-0038-1646151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology of Hemophilia B

Abstract: I ntmduction Gene structure of factor IX Hemophilia B (Christmas disease, Factor IX deficiency, Plasma Thrornboplastin Component [PTC] Deficiency) is an hereditary hemorrhagic disorder that is inherited as an Xlinked recessive characteristic. It occurs in mild, moderate and severe forms, and is clinically indistinguishable from hemophilia A (classic hemophilia) (1). Hemophilia B was serendipitously distinguishcd from classic hemophilia in 1947 (2); Paviovsky noted that when he mixed the blood of one severe hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 30 publications
(10 reference statements)
1
39
0
Order By: Relevance
“…EGF-like domains are thought to be mediators of protein-protein interactions by conservation of this function from EGF. A physiological contribution of the EGF-like domains is suggested by the finding that mutations occurring within these domains are associated with a bleeding tendency (3,16). There has been a recent interest in further characterizing these domains and determining their contribution to FIX(a) procoagulant functions.…”
Section: Fig 2 Analysis Of Purified Recombinant Fix Proteins By Sdsmentioning
confidence: 99%
See 2 more Smart Citations
“…EGF-like domains are thought to be mediators of protein-protein interactions by conservation of this function from EGF. A physiological contribution of the EGF-like domains is suggested by the finding that mutations occurring within these domains are associated with a bleeding tendency (3,16). There has been a recent interest in further characterizing these domains and determining their contribution to FIX(a) procoagulant functions.…”
Section: Fig 2 Analysis Of Purified Recombinant Fix Proteins By Sdsmentioning
confidence: 99%
“…While an E78K point mutation resulted in an impaired interaction with FVIIIa, an R94D point mutation did not result in a functional deficiency (36). 3 Subsequent investigations have determined that the R94S substitution introduces a carbohydrate modification to this site and accounts for the functional impairment of the R94S substitution (35) in the hemophilia B patient. The normal behavior of FIXaR94D suggests a compensation mechanism that allows the R94D protein to function normally while the E78K protein is impaired.…”
Section: Fig 2 Analysis Of Purified Recombinant Fix Proteins By Sdsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Severe deficiency in FIX leads to bleeding (Hemo-philia B, Christmas disease). 15 Lollar and Fass 16 showed that active-site blocked factor IXa (FIXai) inhibits clot formation in vitro.…”
mentioning
confidence: 99%
“…F9 gene is located on the long arm of chromosome X at band Xq27.1-q27.2. 461-residue pre-pro-protein is translated from 2802bp mRNA and subsequently cleaved to the 415-residue mature protein when undergoes a serial of posttranslational modifications [2,3]. FIX protein compose of c-carboxyglutamic acid-rich (Gla) domain, 2 epidermal growth factor-like domains (EGF1 and EGF2) and serine protease (SP) domain.…”
Section: Introductionmentioning
confidence: 99%